N′-(3-Bromo-5-chloro-2-hydroxybenzylidine)-2-hydroxybenzohydrazide - Yehye, Wagee A. (International Union of Crystallography, 2008)
In the approximately planar title molecule, C(14)H(10)BrClN(3)O(2), the dihedral angle between the aromatic ring planes is 5.79 (12)°. The conformation is stabilized by intramolecular O—H⋯N and N—H⋯O hydrogen bonds and an intermolecular O—H⋯O link leads to chains in the crystal propagating in [001].